MEMPERKUAT KETERAMPILAN DIGITAL PENGABDIAN MASYARAKAT MELALUI WORKSHOP INSTALASI SISTEM OPERASI WINDOWS - Iis Aisyah; Aulia Ikhsan; Cendra Harmon (Abdi Jurnal Publikasi, 2024)
The Windows operating system installation workshop at the Nafidatunnajah Islamic Boarding School is a manifestation of the implementation of the Tri Dharma of Higher Education and a real effort to improve digital literacy among students and teachers. This activity aims to introduce the basic concepts of operating systems and provide a practical understanding of their installation, so that participants can master the technological skills needed in the modern era. This workshop plays an important role in addressing the digital divide, especially in Islamic boarding schools that may have limited access to technology. Through collaboration with higher education institutions, such as lecturers from the Informatics Engineering study program at Pamulang University, this activity can be carried out more effectively. The material presented focuses on the installation of the Windows operating system, with the hope that students will gain a deep understanding of information and communication technology and improve their digital skills. The expected outputs of this activity include scientific publications in reputable journals that can be used as references by other schools in addressing the lack of technology utilization. In addition, it is hoped that Islamic boarding school students will be able to design accurate and interesting information, increasing competitiveness in the world of work. The scientific journal articles produced are also expected to contribute to the development of science in the field of community service and local community empowerment.